Exploring the drivers of service quality perceptions in the tertiary education sector. (28th October 2014) - Chavan, Meena; Bowden-Everson, Jana; Lundmark, Erik; Zwar, Jan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper was to identify similarities and differences between domestic and international student's expectations of their tertiary experience, as well as the way in which they evaluate the quality of the service that they receive from their tertiary provider. The paper develops an augmented model of service quality which is adapted to suit the tertiary education context. Design/methodology/approach – The study adopted a qualitative research approach. A total of six focus groups were conducted with a total of 36 International students and domestic students. All students were enrolled in the third year of an undergraduate degree at one large metropolitan university in Australia. The data were analyzed using qualitative analytic techniques and coded using NVIVO. Findings – First, the study found that there are significant challenges with regard to the use of student expectations as the foundation for assessing students' service quality evaluations. This is because students were found to have vague expectations, and limited prior experience of the service from which to shape their expectations. In addition students were found to form their expectations as they consumed the service, throughout their degree program which often spanned three to four years. Second, the study found that traditional dimensions of service quality were not sufficient to capture the depth of international and domestic students' service evaluations. The study proposed the inclusion of an additional two service quality constructs, namely, social benefits and co-creation/participation. Originality/value – Two new dimensions of service quality emerged from this study, "Social benefits" and "Co-creation/Participation". The study therefore suggests that the tertiary experience should be enhanced through the provision of additional opportunities for student to staff and student to student interactions. In addition, tertiary institutions should also enhance opportunities for engagement within both the academic and industry environment.